Perioperative risk stratification in non cardiac surgery: role of pharmacological stress echocardiography - Sicari, Rosa (BioMed Central, 2004)
Perioperative ischemia is a frequent event in patients undergoing major non-cardiac vascular or general surgery. This is in agreement with clinical, pathophysiological, and epidemiological evidence and constitutes an additional diagnostic therapeutic factor in the assessment of these patients. Form a clinical standpoint, it is well known that multidistrict disease, especially at the coronary level, is a severe aggravation of the operative risk. From a pathophysiological point of view, however, surgery creates conditions able to unmask coronary artery disease. Prolonged hypotension, hemorrhages, and haemodynamic stresses caused by aortic clamping and unclamping during major vascular surgery are the most relevant factors endangering the coronary circulation with critical stenoses. From the epidemiological standpoint, coronary disease is known to be the leading cause of perioperative mortality and morbidity following vascular and general surgery: The diagnostic therapeutic corollary of these considerations is that coronary artery disease – and therefore the perioperative risk – in these patients has to be identified in an effective way preoperatively.